Integrated Phytomineral Synergy: The Essential Role of Oligoelements (Mg, Fe, K) in the Antioxidant and Anti-infective Activities of Myrothamnus moschatus - Hanitriniaina, Natafita Carène; Razafimahatratra, Jean Hugues; Soavina, Silvère Augustin; Manjovelo, Christian Sambany; Ngbolua, Koto-Te-Nyiwa Jean Paul; Fatiany, Pierre Ruphin; Rahelivololoniaina, Baholy Robijaona (Budapest International Research and Critics University, 2025)
Myrothamnus moschatus, commonly known as the